2021
DOI: 10.21470/1678-9741-2020-0162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Antioxidant Enzyme Activities, Total Sialic Acid and Trace Element Levels in Coronary Artery Bypass Grafting Patients

Abstract: Introduction In this study, patients before and after cardiac surgery with cardiopulmonary bypass (CPB) and control subjects were evaluated for erythrocyte glutathione peroxidase, catalase and superoxide dismutase enzyme activities, in addition to glutathione, malondialdehyde, serum total sialic acid, lipid-bound sialic acid, total antioxidant status, trace elements and mineral levels. The correlation of these variables with coronary artery disease (CAD) was also assessed. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…At the same time, our study revealed an increase in the concentration of GSH in relation to the concentration of Hb in the postoperative period, which is, apparently, the body’s response to blood loss, damage to chest tissues, and cardiac ischemia–reperfusion during CABG. This is also consistent with the results of [ 53 ], where an increase in the concentration of GSH in erythrocytes was found seven days after CABG. At the same time, however, this indicator remained lower than in the control group, and in patients with acute myocardial infarction, the level of bGSH in RBCs was higher than in healthy volunteers [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, our study revealed an increase in the concentration of GSH in relation to the concentration of Hb in the postoperative period, which is, apparently, the body’s response to blood loss, damage to chest tissues, and cardiac ischemia–reperfusion during CABG. This is also consistent with the results of [ 53 ], where an increase in the concentration of GSH in erythrocytes was found seven days after CABG. At the same time, however, this indicator remained lower than in the control group, and in patients with acute myocardial infarction, the level of bGSH in RBCs was higher than in healthy volunteers [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have investigated sialic acid levels in individuals with AS or those at high risk of AS [30,31,[33][34][35][36][37][38][39]. The results showed that sialic acid levels in patients with heart failure, acute coronary syndrome, coronary atherosclerosis, type 2 diabetes mellitus and hyperlipidemic were higher than the relative control group (Table 1), further confirmed that sialic acid could be a potential metabolic maker to indicate the disease progression as we reported previously.…”
Section: Scfea Analysis Highlighted Glycolysis/hexosamine/sialic Acid...supporting
confidence: 86%
“…Likewise, PAB is considered a comprehensive biomarker measuring concurrently plasma pro-oxidant activity and antioxidant capacity, and it has already been recommended as a convenient parameter for oxidative stress evaluation in patients with STEMI by various groups [ 33 , 34 , 35 ]; higher values of PAB point to the increased levels of oxidative stress. On the other side, decreased TAS values were noticed in several CAD studies [ 36 , 37 ], but its predictive ability has not been reported until now. Different studies reported short LTL as an independent predictor of short-term major adverse cardiovascular events (MACEs) and long-term outcomes in CAD patients.…”
Section: Discussionmentioning
confidence: 95%